Defence Industry Policy of Indonesia: A Lesson Learned from India - Huliyani, Tri; Perwita, Anak Agung Banyu; Ramsi, Oktaheroe (International Journal of Humanities, Education, and Social Sciences, 2025)
National defence industry self-reliance has become a strategic imperative for states globally, particularly in an international system characterized by anarchy and self-help dynamics. Within this context, the state emerges as the central actor in safeguarding its sovereignty, and the pursuit of defence industry autonomy represents a key survival strategy. This study analyzes Indonesia’s defence industry policy through the theoretical lenses of realism, the developmental state, and the triple helix framework, drawing comparative insights from India, a country widely regarded as more advanced in this sector. Both Indonesia and India are major emerging powers in the Global South with shared ambitions for defence self-reliance, yet they demonstrate divergent trajectories in institutional capacity and policy outcomes, making them suitable for comparative analysis. Employing a qualitative case study design, the research utilizes secondary data from official documents, academic literature, research institute reports, and credible media sources. The findings indicate that while Indonesia benefits from a solid legal foundation (notably Law No. 16/2012) and political commitment, its defence industrial development is hindered by limited fiscal allocations, the dominance of state-owned enterprises, underdeveloped industrial research capabilities, and weak synergy within the triple helix model. Conversely, India has advanced its defence sector through strategic initiatives such as Make in India and Atmanirbhar Bharat, underpinned by fiscal incentives, deregulation, increased private sector engagement, enhanced research through the Defence Research and Development Organisation (DRDO), and a well-integrated triple helix innovation ecosystem. These comparative insights underscore the need for Indonesia to reform its policy paradigm by strengthening its industrial roadmap, fostering private sector participation, enhancing government–industry–academia collaboration, and pursuing export-oriented and technology transfer strategies. Theoretically, the study contributes to the growing literature on defence industry development in emerging states; practically, it offers policy recommendations aimed at improving Indonesia’s defence industrial ecosystem, enhancing global competitiveness, and reducing import dependency through innovation-led self-reliance.